Inverted Fuel Cell: Room‐Temperature Hydrogen Separation from an Exhaust Gas by Using a Commercial Short‐Circuited PEM Fuel Cell without Applying any Electrical Voltage1. Issue 27 (26th May 2015) - Friebe, Sebastian; Geppert, Benjamin; Caro, Jürgen
Abstract A short‐circuited PEM fuel cell with a Nafion membrane has been evaluated in the room‐temperature separation of hydrogen from exhaust gas streams. The separated hydrogen can be recovered or consumed in an in situ olefin hydrogenation when the fuel cell is operated as catalytic membrane reactor. Without applying an outer electrical voltage, there is a continuous hydrogen flux from the higher to the lower hydrogen partial pressure side through the Nafion membrane. On the feed side of the Nafion membrane, hydrogen is catalytically split into protons and electrons by the Pt/C electrocatalyst. The protons diffuse through the Nafion membrane, the electrons follow the short‐circuit between the two brass current collectors. On the cathode side, protons and electrons recombine, and hydrogen is released.